Atypical lesions and infection sites of larval trematodes in marine gastropods from Argentina - Gilardoni, Carmen Mariangel (2018)
This study documents the lesions caused by 9 digenean larvae parasitizing 6 marine gastropod species from Patagonia, Argentina. Most digeneans produce a lesion where the parthenitae replace the gonadal tissues and also occupy part of the digestive gland. Three atypical lesions and tropism were observed in (1) Trophon geversianus (Muricidae) infected by Renicolidae gen. et sp. 1, where the sporocysts occur inside the gonad acini which retain their general structure due to the persistence of the acinus wall, (2) Nacella magellanica (Nacellidae) infected by Renicolidae gen. et sp. 2, where the gonad is not affected and the sporocysts are located only among the digestive gland tubules, and (3) Siphonaria lessonii (Siphonariidae) infected by Schistosomatidae gen. et sp., where fully developed cercariae occur inside the digestive tubules. At high infection intensities or in double infections, larvae can invade other organs (mantle, foot or gill) and, on occasion, may elicit hemocytic encapsulation.